ANALYSIS OF HIGH SCHOOL STUDENTS LOGICAL-MATHEMATICAL THINKING ABILITY BASED ON THE POLYA STAGE SOLVING IN TERMS OF MATHEMATICAL SELF-CONCEPT ABILITY - Rika Mulyati Mustika Sari; Nanang Priatna; Dadang Juandi (Prima: Jurnal Pendidikan Matematika, 2022)
This research is based on the importance of logical-mathematical thinking skills in solving logical-mathematical problems. The research purpose is to describe high school students' logical thinking abilities on geometric transformation material in terms of mathematical self-concepts. The research used a qualitative approach, with the research subject as many as six students of 12th grades science class from one of Bandung Regency high schools selected by sampling technique. Students' logical thinking ability is known from the test scores in solving compiled problems. The score refers to logical-mathematical thinking ability indicators, and the problem-solving technique refers to the Polya stages. Data analysis techniques used are data reduction, data presentation, descriptive statistical calculations, and conclusions/verification. The results showed that the overall students’ logical-mathematical thinking ability in the geometry transformation material is in the medium category. In the self-concept category, subjects with high self-concept can fulfil logical thinking questions based on Polya stages. As for subjects with moderate self-concept, the students can only fulfil several indicators of logical-mathematical thinking skills with problem-solving techniques. The result is still not perfect refer to the Polya stage. As for the subject with low self-concept, almost all Polya stages are not fulfiled. The students in the low self-concept category answered the questions incompletely. They had difficulty understanding the problem and planning a solution so that their answers did not match the questions.